2020
DOI: 10.1093/cvr/cvaa234
|View full text |Cite
|
Sign up to set email alerts
|

Human CD16+ monocytes promote a pro-atherosclerotic endothelial cell phenotype via CX3CR1–CX3CL1 interaction

Abstract: Aims Monocytes are central for atherosclerotic vascular inflammation. The human non-classical, patrolling subtype, which expresses high levels of CD16 and fractalkine receptor CX3CR1, strongly associates with cardiovascular events. This is most marked in renal failure, a condition with excess atherosclerosis morbidity. The underlying mechanism is not understood. This study investigated how human CD16+ monocytes modulate endothelial cell function. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…This cell type expresses CX3CR1 on its surface. The amount of surface CX3CR1 per individual monocyte was decreased in CKD in some (Liakopoulos et al 2018), but not other studies (Roy-Chowdhury et al 2020). In a gene expression analysis of human monocytes, both, the nonclassical monocyte marker CD16 and CX3CR1, were expressed at significantly higher levels on monocytes in patients with chronic kidney disease and cardiovascular events compared to all other groups (Schepers et al 2015).…”
Section: Systemic Regulation Of Cx3cr1 + Cells In Chronic Kidney Diseasementioning
confidence: 66%
See 1 more Smart Citation
“…This cell type expresses CX3CR1 on its surface. The amount of surface CX3CR1 per individual monocyte was decreased in CKD in some (Liakopoulos et al 2018), but not other studies (Roy-Chowdhury et al 2020). In a gene expression analysis of human monocytes, both, the nonclassical monocyte marker CD16 and CX3CR1, were expressed at significantly higher levels on monocytes in patients with chronic kidney disease and cardiovascular events compared to all other groups (Schepers et al 2015).…”
Section: Systemic Regulation Of Cx3cr1 + Cells In Chronic Kidney Diseasementioning
confidence: 66%
“…Interestingly, the increase in this cell type is reversible with kidney transplantation (Ulrich et al 2008;Vereyken et al 2013;Sekerkova et al 2014;Roy-Chowdhury et al 2020). This suggests that the phenotype is related to uremia, rather than the presence of a damaged kidney.…”
Section: Systemic Regulation Of Cx3cr1 + Cells In Chronic Kidney Diseasementioning
confidence: 99%
“…During atherosclerosis, monocytes expressing CX3CR1 bind and adhere to the endothelium, which expresses mCX3CL1 [ 138 ]. Certainly, CD16 + CX3CR1 HIGH monocytes enhanced endothelial STAT1 and NFκB p65 phosphorylation resulting in an upregulated expression of CX3CL1 and IL-1β, and ICAM1 and VCAM1, compared to classical CD14 + monocytes [ 139 ]. This describes the mechanism by which CX3CR1 and its ligands can increase cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…We found that PLWH had an increased expression and density of CX3CR1 on total monocytes as well as across the three monocyte subsets. The CX3CR1 chemokine receptor is involved in adhesion and migration of monocytes into the tissues, and has an important role in atherogenesis and plaque development [27,28]. Whether CX3CR1 expression is enhanced in PWLH on chronic ART has been under debate.…”
Section: Discussionmentioning
confidence: 99%